The Effect of Chatbot Services on Online Shop Customer Satisfaction: The Effect of Chatbot Services on Online Shop Customer Satisfaction - Cecep M Kappi Kappi; Lina Marlina (Brilliance: Research of Artificial Intelligence, 2023)
The increasing trend of e-commerce users has not been matched by customer satisfaction in the shopping process. Indonesia has the highest level of dissatisfaction compared to other ASEAN countries. Although chatbot technology has been used as an aid to optimize services, dissatisfaction still occurs with regard to agility, service assurance, reliability, scalability and security. The purpose of this study is to determine chatbot services in providing customer satisfaction. The research approach uses quantitative with explantory survey method. The research population is online shop users using rondom sampling, 175 respondents were collected. Assisted by PLS SEM analysis tool. The results show that chatbot social orientation services contribute to online shop customer satisfaction. Likewise, chatbot personification makes a positive contribution to online shop customer satisfaction.